Factors Influencing Chemotherapy Adherence in Patients with Triple-Negative Breast Cancer: A Cross-Sectional Study at the National Cancer Center, Dharmais Hospital, Indonesia - Suryana, Kresna Dharma; Girsang, Ermi; Nasution, Sri Lestari Ramadhani; Tadjoedin, Hilman; Anjasari, Melati Salsabila (http://dharmais.co.id/, 2025)
Background: Triple‑negative breast cancer (TNBC) is an aggressive subtype of breast malignancy with limited targeted therapy options, making adherence to systemic therapy critical for improving survival outcomes. This study aimed to determine the sociodemographic, clinical, and psychosocial factors influencing adherence to systemic therapy among patients with TNBC, especially in resource-constrained settings.Method: A cross-sectional observational study was conducted among 105 female TNBC patients undergoing systemic therapy at the Dharmais Cancer Hospital. Adherence was defined as completion of ≥ 85% of planned systemic therapy cycles without unjustified delay or omission. Data were collected from medical records and structured questionnaires, covering sociodemographic, clinical, and psychosocial characteristics, including psychological distress measured using the Depression Anxiety Stress Scale-10 (DASS-10). Bivariate and multivariate logistic regression analyses were performed to identify factors associated with non-adherence.Results: Median patient age was 48 years (range 25–76), and the majority worked as housewives (58.1%). Most had completed high school education (51.5%), and nearly half earned less than IDR 3 million monthly (48.6%). Clinically, most patients were diagnosed at stage III (40.9%) or IV (38.1%), with comorbidities present in 41.9%, predominantly hypertension (19.1%). While overall adherence to systemic therapy was relatively high, logistic regression analysis identified significant predictors of non-adherence. Comorbid conditions (p 0.01; OR 5.7; 95% CI: 1.94–16.02) and severe levels of anxiety/depression based on DASS-10 scores (p = 0.015; OR 5.65; 95% CI: 1.08–29.42) remained independently associated with lower adherence (p 0.05), underscoring the importance of psychological and clinical support to improve treatment compliance.Conclusion: Comorbid conditions and psychological distress significantly contribute to non-adherence among TNBC patients. Integrating psycho-oncology support and comorbidity management into routine cancer care may enhance treatment adherence and outcomes.